2021
DOI: 10.1186/s12877-021-02511-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the tailored activity program (TAP) on dementia-related symptoms, health events and caregiver wellbeing: a randomized controlled trial

Abstract: Background People living with dementia (PLWD) and caregivers are adversely impacted by lack of meaningful activity leading to worse symptoms and impaired quality-of-life. There is a critical need to develop effective and well-tolerated treatments that mitigate clinical symptoms, engage PLWD and support caregiver wellbeing. We tested whether, compared to attention control, the Tailored Activity Program (TAP) reduced clinical symptoms and health-related events, and improved caregiver wellbeing, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Moreover, unpaid family members (care partners) often experience stress and burden when caring for persons living with dementia (Ornstein and Gaugler, 2012). Despite these adverse outcomes, studies show participating in meaningful activities can support well-being for persons living with dementia (Oh et al , 2021) and their care partners (Gitlin et al , 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, unpaid family members (care partners) often experience stress and burden when caring for persons living with dementia (Ornstein and Gaugler, 2012). Despite these adverse outcomes, studies show participating in meaningful activities can support well-being for persons living with dementia (Oh et al , 2021) and their care partners (Gitlin et al , 2021).…”
mentioning
confidence: 99%
“…Zgola (1999) defines meaningful activity as purposeful, voluntary, socially appropriate, feeling good to participants and imparting a sense of success. Meaningful activity is linked to well-being for persons living with dementia (Gitlin et al , 2021). Well-being comprised the following: positive emotions; engagement (completely absorbed in an activity); relationships; meaning (belonging and serving beyond oneself); and accomplishment (PERMA) that collectively contributes to human flourishing (Seligman, 2011).…”
mentioning
confidence: 99%
“…The trial design and Consort study flowchart were reported previously 25,26 . TAP was evaluated in a single‐blind 2‐arm randomized controlled trial conducted in Baltimore, Maryland.…”
Section: Methodsmentioning
confidence: 99%
“…TAP provides activities tailored to the interests and abilities of people living with dementia (PLWD) and instructs caregivers in their use. However, treatment effects for BPSD across TAP trials are inconsistent with some, but not all, studies reporting reductions 21–26 . In a recent trial of 250 dyads, TAP did not reduce agitation and aggression‐type behaviors, the main trial outcome, although other benefits were found 26 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation